Securing Cloud Computing Services with an Intelligent Preventive Approach - Altowaijri, Saleh M.; El Touati, Yamen (Engineering, Technology & Applied Science Research, 2024)
Cloud computing is a technological marvel that transcends conventional boundaries by utilizing an Internet-based network of remote servers to store, manage, and process data and many other services. It represents a contemporary paradigm for delivering information technology services. Today, cloud computing services have become indispensable for both individuals and corporations. However, adopting cloud services presents fresh challenges in terms of service quality, resource optimization, data integration, cost governance, and operational security. The security of cloud services is of supreme importance, given the open and distributed nature of the environment, making it susceptible to various cyberattacks, such as Denial of Service (DoS) or Distributed DoS (DDoS) attacks, among others. Cyberattacks can have severe repercussions on the availability of cloud services, potentially causing complete DoS. In numerous instances, the detection of attacks is delayed, pushing cloud platforms to a breaking point. Emphasizing the importance of proactive measures, it becomes crucial to identify and alert about any suspicious access long before the latter reaches a critical stage, mitigating the risks and preventing potential service disruptions. This study introduces a preventive approach that utilizes artificial intelligence techniques to improve the security of cloud services. The proposed method aims to detect and flag potential attack behaviors well in advance before they affect service quality. To achieve this, the particular method involves periodic identification and measurement of critical information on service access and resource utilization. This can be accomplished by analyzing cloud server logs or integrating dedicated sniffing software to capture and store technical traffic details. Subsequently, the collected data are processed by analyzing traffic properties to proactively identify and report any indications of cyberattacks.